PENGARUH SELF EFFICACY DAN TOLERANCE FOR RISK TERHADAP MINAT ENTREPRENEURSHIP (STUDI PADA MAHASISWA MANAJEMEN FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS KHAIRUN) - Afniati, Afniati; W. Jabid, Abdullah (Jurnal Manajemen Sinergi, 2023)
ABSTRACTObjective: This research aims to determine the influence of product quality and price on purchasing decisions mediated by word of mouth in the case of the Puta Dino Tidore weaving house.Methodology: The population in this research is students from the Management Study Program, Faculty of Economics and Business, Khairun University class 2019-2021, totaling 547 people. The sampling technique used in this research is probability sampling, with a simple random sampling method so that the sample is 231 students.Findings: Partial hypotheses and simultaneous and partial hypotheses are accepted, because the alpha value is smaller than 5%.Conclusion: The results of the research show that self-efficacy has a positive and significant effect on the entrepreneurship interest of students in the Management Study Program, Faculty of Economics and Business, Khairun University, Ternate, which means that the higher the self-efficacy; and Tolerance for risk has a positive and significant influence on students' interest in entrepreneurship in the Management Departement, Faculty of Economics and Business, Khairun University, Ternate, which means that with tolerance for riskÂ